Pengaruh Kompetensi Pedagogik, Kompetensi Profesional Dan Kepuasan Kerja Terhadap Kinerja Guru Di Sma Islam Bakti Asih - Frando Christo Wulur; Dendy Bagaskara; Ahya nurdin; Wulan Auliyani; Vip Paramarta (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
A teacher's professional performance is influenced by several factors such as competence and job satisfaction. Ideally, the competencies that a teacher must have are pedagogical, professional, social and personality competencies. Meanwhile, job satisfaction is related to standards or measures of fulfilling the work rights and obligations of a teacher. The factors determining the success of teacher performance have not yet been clarified regarding which factors have a stronger influence on teacher professional performance. Through this research, clarity will be found on this problem. This research aims to determine the influence of pedagogical competence, professional competence, and job satisfaction on teacher performance. This research is correlational research because it will test the influence of the independent variable on the dependent variable. There are two approaches used, namely a qualitative approach and a quantitative approach. The research was carried out at BAKTI ASIH ISLAM SMA. The data in this research is divided into (1) teacher professional competency data, (2) teacher pedagogical competency data, (3) job satisfaction data, and (4) teacher performance data. Data collection techniques include observation, interviews, questionnaires and documentation techniques. Data analysis includes, (1) analysis of test item validity, (2) analysis of instrument reliability test, (3) data requirements test including normality test and linearity test, (4) descriptive analysis, (5) hypothesis test with Partial T test and F test.